Lung function decline is accelerated in South Africans with cystic fibrosis - R. Masekela; S. Olorunju; R. J. Green; N. T. Magidimisa (South African Family Practice)
Background: Poor nutritional status has been shown to be associated with a significant decline in lung function in patients with cystic fibrosis. There are few data published on the lung function decline and the effects of nutritional status in cystic fibrosis (CF) in South Africa.